Campylobacter Colitis as a Trigger for Atypical Hemolytic Uremic Syndrome: About One Case - Thomas Quinaux; Zead Tubail; Isabelle Vrillon; Hervé Sartelet; Benjamin Savenkoff (Case Reports in Nephrology and Dialysis, 2023)
We present the case of a 17-year-old Caucasian male whose condition featured acute renal failure, anemia, and deep thrombocytopenia after five consecutive days of diarrhea. Campylobacter coli was identified in stool cultures and, although the direct role of this germ in the pathogenesis of hemolytic uremic syndrome (HUS) remains uncertain to this day, initial presentation was considered broadly consistent with typical HUS. However, the patient showed no signs of spontaneous recovery over time. While secondary investigations showed no abnormalities in ADAMTS13 activity or in the alternate pathway of complement, patient’s condition deteriorated. Worsening kidney failure required emergency renal replacement therapy and was followed by cardiac involvement in the form of acute heart failure. Given this unfavorable development, blood samples were drawn to look for mutations in the alternate complement pathway, and eculizumab therapy was initiated without further delay, allowing prompt improvement of cardiac function and recovery of diuresis. Upon discharge, the patient still had to undergo intermittent dialysis, which would later be withdrawn. Genetic analysis ultimately confirmed the presence of a complement factor H mutation associated with a high risk of disease recurrence, indicating long-term continuation of eculizumab therapy.